Front Cover: Bilberry Supplementation after Myocardial Infarction Decreases Microvesicles in Blood and Affects Endothelial Vesiculation. Issue 20 (19th October 2020) - Bryl‐Górecka, Paulina; Sathanoori, Ramasri; Arevström, Lilith; Landberg, Rikard; Bergh, Cecilia; Evander, Mikael; Olde, Björn; Laurell, Thomas; Fröbert, Ole; Erlinge, David
Abstract : Mol. Nutr. Food Res . 2020, 64, 2000108 DOI: 10.1002/mnfr.202000108 Bilberries are considered beneficial in cardiovascular diseases (CVD), however the mechanisms of cardioprotection are poorly understood. CVD is characterized by high levels of circulating microvesicles in blood. Bilberry extract supplementation for eight weeks in myocardial infarction patients decreased levels of endothelial and platelet‐derived MVs. Bilberry extract treatment of endothelial cells reduced vesiculation through molecular mechanisms related to the P2X7 receptor. This is reported by Paulina Bryl‐Górecka, Ramasri Sathanoori, Lilith Arevström, Rikard Landberg, Cecilia Bergh, Mikael Evander, Björn Olde, Thomas Laurell, Ole Fröbert, and David Erlinge in article 2000108 .